THE ROLE OF PRIVATE MANAGEMENT COMPANIES IN THE MODERN PENSION SYSTEM OF RUSSIA - T. Gorbacheva; G. Fatkhlislamova (Вестник университета, 2018)
The results of the research of the dynamics and structure of investing of pension savings funds by private managers for the period from 2004 to 2017 are presented. The dynamics of the market value of investment portfolios of private management companies, the structure of their investments in various types of assets has been analyzed, the dynamics of changes in the structure of assets for 2004-2017 has been estimated. The nature of the investment strategy of investing the funds of pension savings of private capital has been revealed, as well as the main factors that have influenced the structure of their main investments in various assets. The key tendencies of the development of the mandatory pension insurance system are determined in the course of exercising the functions of trust management of private pension funds by individuals.